2016
DOI: 10.1021/acsomega.6b00055
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Cellulose Nanocrystals with PEG-Metal-Chelating Block Copolymers via Controlled Conjugation in Aqueous Media

Abstract: Elongated nanoparticles have recently been shown to have distinct advantages over their spherical counterparts in drug delivery applications. Cellulose nanocrystals (CNCs) have rodlike shapes in nature and have demonstrated biocompatibility in a variety of mammalian cell lines. In this report, CNCs are put forward as a modular platform for the production of multifunctional rod-shaped nanoparticles for cancer imaging and therapy. For the first time, PEGylated metal-chelating polymers containing diethylenetriami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 61 publications
(127 reference statements)
1
34
0
Order By: Relevance
“…There is a growing interest in using CNCs in nanomedicine, due to their biocompatibility, as well as their asymmetric (rod‐like) shape facilitating prolonged blood circulation time and possible cellular uptake . Furthermore, the hydroxyl groups on the CNCs surface are amenable for attachment of polymer molecules or imaging and therapeutic agents . Since C‐dot/CNC NPs can be used as biotags for labeling, sensing, and therapeutics, we examined their biocompatibility by culturing MCF‐7 breast cancer cells for 24 and 48 h in suspensions of hybrid NPs with concentrations from 0.00001 to 0.1 wt% in cell culture media.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing interest in using CNCs in nanomedicine, due to their biocompatibility, as well as their asymmetric (rod‐like) shape facilitating prolonged blood circulation time and possible cellular uptake . Furthermore, the hydroxyl groups on the CNCs surface are amenable for attachment of polymer molecules or imaging and therapeutic agents . Since C‐dot/CNC NPs can be used as biotags for labeling, sensing, and therapeutics, we examined their biocompatibility by culturing MCF‐7 breast cancer cells for 24 and 48 h in suspensions of hybrid NPs with concentrations from 0.00001 to 0.1 wt% in cell culture media.…”
Section: Resultsmentioning
confidence: 99%
“…Since C‐dot/CNC NPs can be used as biotags for labeling, sensing, and therapeutics, we examined their biocompatibility by culturing MCF‐7 breast cancer cells for 24 and 48 h in suspensions of hybrid NPs with concentrations from 0.00001 to 0.1 wt% in cell culture media. Notably, the highest tested concentration was at least, tenfold higher than the highest concentration tested for biocompatibility of composite CNC NPs . In the control experiment, the cells were cultured in the cell culture media without exposure to C‐dot/CNC NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary evaluations have demonstrated that PEGylated CNCs are nontoxic for human ovarian cancer cell line (HEYA8). 34 Also, poly(2-aminoethylmethacrylate)- g -CNC toxicity was evaluated against mouse monocyte cells (J774A1) and human breast adenocarcinoma cells (MCF-7). 35 Even if no cytotoxicity to J774A1 cells was observed, an unexpected increase in 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide reduction was observed, requiring further investigations and demonstrating that such evaluations must be performed carefully case by case.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Covalent Attachment of Fluorescein Isothiocyanate to Cellulose Nanocrystals: The surface of CNCs was chemically modified with FITC dye, as described elsewhere. [43] Briefly, epichlorohydrin (5.8 mL, 0.28 mol g −1 CNC) was added to the mixture of 10 mL of 2.65 wt% of CNC suspension with 25 mL of 1 m NaOH (aq). The reaction mixture was stirred at 60 °C for 1 h, centrifuged (4000 × g for 10 min), and diluted with water, until the pH = 12 was reached (pH meter, Mettler Toledo).…”
Section: Methodsmentioning
confidence: 99%